Changes in cholesterol and its precursors during the first days after major trauma - Bakalar, Bohumil; Hyspler, Radovan; Pachl, Jan; Zadak, Zdenek (Wiener klinische Wochenschrift, 2003)
BACKGROUND: The causes of hypocholesterolemia in the critically ill, including major trauma patients, have not yet been fully elucidated. OBJECTIVE: We tested the hypothesis that hypocholesterolemia is caused by decreased production of cholesterol precursors. DESIGN: Serum concentrations of squalene, lanosterol, and lathosterol were measured on admission, and then at 24 and 48 hours after injury using gas chromatography coupled with mass spectrometry. Serum concentrations of total low-density and high-density lipoprotein cholesterol were measured on admission and every day in the first week after injury. RESULTS: 83 consecutive patients with multiple trauma were examined. Significant drops in concentrations of lanosterol and lathosterol were found in the patients in comparison with the control group. The most profound drop was in lathosterol. CONCLUSION: Decreased synthesis of cholesterol precursors is the major cause of hypocholesterolemia in patients with multiple trauma. Lathosterol concentration is proposed as a marker of cholesterol synthesis.
Keywords: Analysis of Variance; dospělí; polytrauma; logistické modely; cholesterol; Chromatography, Gas; Female; hypercholesterolemie; LDL-cholesterol; kritický stav; Adult; Cholesterol, LDL; ženské pohlaví; Logistic Models; Adolescent; Multiple Trauma; Time Factors; časové faktory; lidé; péče o pacienty v kritickém stavu; Critical Care; hmotnostní spektrometrie; Cholesterol; Squalene; Humans; analýza rozptylu; Hypercholesterolemia; Male; Aged; skvalen; chromatografie plynová; HDL-cholesterol; Mass Spectrometry; lidé středního věku; senioři; mužské pohlaví; lanosterol; Lanosterol; Middle Aged; mladiství; Critical Illness; Cholesterol, HDL